Amitav Acharya – Barry Buzan (eds.): Non-Western International Relations Theory: Perspectives on and beyond Asia. - Miroslav Jurásek (Czech Journal of International Relations, 2012)
Amitav Acharya – Barry Buzan (eds.): Non-Western International Relations Theory: Perspectives on and beyond Asia. 1st ed. London: Routledge, 2010, 242 stran, ISBN 978-0-415-47474-0 (signatura knihovny ÚMV 56 901).